Humour Runs through the Multicoloured Mosaic of Neuropsychotherapy: Scoping Review - M. Šeduikienė; V. Matonis (Neurologijos seminarai, 2024)
Background. The investigation is devoted to explore the possibilities of humour to treat neuropsychiatric disorders which, in the last decade, have significantly increased. The aim of the study is to describe the growing investigations, in which various styles and forms of humour are used in the treatment of neuropsychiatric disorders, and to evaluate their therapeutic peculiarities. Overall research question. What is the role of humour in the treatment of neuropsychiatric disorders? Material and methods. Scientific investigations were analysed, grouped, interpreted and generalized. Information for literature review was collected in the PubMed and Google Scholar databases. Overall, 25 articles published between 2013 and 2023 and written by 171 authors (from 28 countries) were analysed. Results. The investigations concisely reviewed herein are associated with the only therapeutic form – the usage of humour in the treatment of neuropsychiatric disorders. The results of the investigations are divided into five sections: the use of humour in the context of different coping strategies (5 investigations); the use of only humour in the treatment (6 investigations); the use of the styles of humour in the treatment (5 investigations); comprehension of humour by patients (6 investigations), and clinical trials which revealed the sense of humour in the brain of patients (4 investigations). Conclusions. The results of the reviewed investigations showed that the therapeutic potential of humour is high enough to broaden the horizon of neurology to some extent. The growing popularity of humour usage in the treatment of neuropsychiatric disorders could encourage this kind of therapeutic activity in Lithuania as well.